Representation in State Legislatures - Jewell, Malcolm E., 1928-2010 (Book collections on Project MUSE., 1982)
Every two years American voters turn out to elect several thousand representatives to state legislatures. Only now in Representation in State Legislatures do we have a detailed examination of how these officials perceive their jobs and how they attempt to do them. To provide answers to these questions, Malcolm E. Jewell conducted intensive interviews with 220 members of houses of representatives in nine selected states. He asked each legislator how he kept in touch with his constituents, how he resolved matters of policy, how he sought government resources for his district, and what services.